2008
DOI: 10.1016/j.ydbio.2007.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of cell-cycle quiescence during C. elegans development

Abstract: During the development of the C. elegans reproductive system, cells that give rise to the vulva, the vulval precursor cells (VPCs), remain quiescent for two larval stages before resuming cell division in the third larval stage. We have identified several transcriptional regulators that contribute to this temporary cell-cycle arrest. Mutation of lin-1 or lin-31, two downstream targets of the Receptor Tyrosine kinase (RTK)/Ras/MAP kinase cascade that controls VPC cell fate, disrupts the temporary VPC quiescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 56 publications
2
60
1
Order By: Relevance
“…CKM subunits have been implicated as regulators of canonical Wnt signaling (Zhang and Emmons 2000;Firestein et al 2008;Morris et al 2008) and cell cycle quiescence (Clayton et al 2008), processes which also contribute to vulva development. Activation of Wnt signaling can bypass requirements for let-23/EGFR in vulva development (Gleason et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CKM subunits have been implicated as regulators of canonical Wnt signaling (Zhang and Emmons 2000;Firestein et al 2008;Morris et al 2008) and cell cycle quiescence (Clayton et al 2008), processes which also contribute to vulva development. Activation of Wnt signaling can bypass requirements for let-23/EGFR in vulva development (Gleason et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Muv phenotype of mdt-12/dpy-22 mutants is independent of bar-1/b-catenin (Moghal and Sternberg 2003b), suggesting that the CKM does not repress vulva development through the canonical Wnt signaling pathway. Deregulation of cell cycle quiescence can expand the VPC equivalence group, which are competent to form ectopic vulvae if presented with the appropriate signals [e.g., lin-12/Notch gain of function employed by Clayton et al (2008)]. Although CKM subunits are required for VPC cell cycle quiescence (Clayton et al 2008), this alone is unlikely to account for the ectopic vulvae observed in these animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of its effects have been attributed to the Cdk8 kinase, which phosphorylates the C-terminal domain of Pol II (22,23), the Cyclin H component of the TFIIH general transcription factor (24), and other subunits of the mediator complex (19), as well as specific transcription factors (25)(26)(27)(28)(29). The large Med12 and Med13 proteins are required for specific developmental processes in Drosophila, zebrafish, and Caenorhabditis elegans (30)(31)(32)(33)(34)(35)(36)(37)(38), but their biochemical functions are not understood.…”
mentioning
confidence: 99%
“…Previous studies have reported the expression pattern of the FoxB gene in hydra, sea urchin, frog and zebrafish (Cheavalier et al, 2006;Gamse and Sive et al, 2001;Clayton et al, 2008;Tu et al, 2006;Minokawa et al, 2004;Grinblat et al, 1998). In vertebrates, the FoxB gene has been used as a marker gene for hindbrain.…”
Section: Introductionmentioning
confidence: 99%